2014
DOI: 10.7314/apjcp.2014.15.1.423
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Colposcopic Diagnosis and Cervical Pathology: Siriraj Hospital Experience

Abstract: Asian Pac J Cancer Prev, 15 (1), [423][424][425][426] IntroductionCervical cancer is the second most common malignancy in women worldwide after breast cancer (Ferlay et al.). In Thailand, its incidence was 17.7/100,000 of Thai female population during (Khunhaprema et al., 2012. Cervical cancer incidences and deaths have decreased since the implementation of widespread cervical cancer screening with cervical cytology and/or human papilloma virus (HPV) (Saslow et al., 2012). The knowledge of HPV has been advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
17
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 15 publications
9
17
4
Order By: Relevance
“…The study results showed that the agreement of the colposcopic diagnosis and cervical biopsy pathology was perfectly matched in 65.5% of lesions, further, the agreement of the colposcopic diagnosis and final pathology was perfectly matched in 66.2% of lesions, with findings significantly better than those of Baum et al and Massad et al (perfect agreement, 32-37%) [ 3 , 4 ]. Tatiyachonwiphut et al [ 13 ] reported an exact agreement of 57.9%, one grade agreement of 94.1%, and a weighted kappa strength of agreement of 0.494, which were comparable to the results of our study. However, the study lacked a standard criterion or scoring system for colposcopic examination.…”
Section: Discussionsupporting
confidence: 91%
“…The study results showed that the agreement of the colposcopic diagnosis and cervical biopsy pathology was perfectly matched in 65.5% of lesions, further, the agreement of the colposcopic diagnosis and final pathology was perfectly matched in 66.2% of lesions, with findings significantly better than those of Baum et al and Massad et al (perfect agreement, 32-37%) [ 3 , 4 ]. Tatiyachonwiphut et al [ 13 ] reported an exact agreement of 57.9%, one grade agreement of 94.1%, and a weighted kappa strength of agreement of 0.494, which were comparable to the results of our study. However, the study lacked a standard criterion or scoring system for colposcopic examination.…”
Section: Discussionsupporting
confidence: 91%
“…Instead, the other three methods were substantially unequivalent between them. This is especially the case with the modified RCI and Swede Score, where the underestimated diagnoses were rather high, consistent with approximately 1/3 of HSIL underdiagnosed colposcopies in other reports [27, 28]. …”
Section: Discussionsupporting
confidence: 89%
“…After an abnormality is detected through cervical screening, a colposcopy is performed . In a previous Siriraj Hospital study, the false‐negative rate using a colposcopy alone was determined to be 19.1% . That study suggested using a cervical biopsy as the gold standard to detect high‐grade lesions.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] In a previous Siriraj Hospital study, the false-negative rate using a colposcopy alone was determined to be 19.1%. 8 That study suggested using a cervical biopsy as the gold standard to detect highgrade lesions. Furthermore, a study from Germany found that the accuracy by colposcopy was only 85.8%.…”
Section: Introductionmentioning
confidence: 99%